CRITICAL DISCOURSE ANALYSIS ON FOREIGN MEDIA NEWS RELATED TO INVESTMENT SCAMS: AN ANALYSIS OF VAN DIJKâ€™S MODEL - Fani Indrawan (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2022)
Van Dijkâ€™s model of critical discourse analysis on foreign media news about â€œThese young Indonesians became rich through 'investment platforms'. They've now been charged with fraudâ€. Van Dijk model consists of macrostructure, superstructure and microstructure. These three structures are used to analyze the discourse of the news text. The results of this research are: 1. The macrostructure of the text describes the theme of